SOSIALISASI PEMILIHAN KEPALA DAERAH (PILKADA 2024) SEBAGAI UPAYA PENGUATAN PARTISIPASI MASYARAKAT DI TINGKAT DESA BLOROK - Dendy Kurniawan; Nur Faizin; Ainul Maftuchah; Sunarto Sunarto; Anwar Anwar; Bagus Sembodo (Jurnal Padamu Negeri, 2024)
The Regional Head Election (Pilkada) is a democratic mechanism that allows citizens to directly elect their regional leaders. However, voter participation in Pilkada remains a challenge, especially in rural areas, due to limited access to information, political apathy, and a lack of political education. This study aims to enhance community participation through the 2024 Pilkada socialization program in Blorok Village, Brangsong District, Kendal Regency, Central Java. The method used in this community engagement activity is political education-based socialization, involving community leaders, neighborhood heads (RT/RW), and local residents. The stages of the activity include planning, preparation of socialization materials, implementation at the village hall, and evaluation of its effectiveness. The evaluation results indicate an increase in public understanding regarding the importance of electoral participation. Participants who previously had little knowledge about the voting process showed greater enthusiasm after attending this program. Despite challenges such as time constraints for participants and skepticism towards the election process, this socialization effort positively impacted political awareness in the community. It is expected that similar initiatives will continue to improve the quality of democracy and encourage active community participation in future elections.